GAMBARAN SISTEM PENGANGKUTAN SAMPAH di UPK BADAN AIR WILAYAH I KOTA ADMINISTRASI JAKARTA TIMUR (Studi Kasus: Kecamatan Pasar Rebo) - Yusriani Sapta Dewi; Syifa Sabrina (JURNAL TECHLINK, 2021)
Waste is a serious environmental problem in Indonesia. DKI Jakarta is one of the cities with the largest waste contributor in Bantargebang Integrated landfills. Water is the fastest carrier ofwaste than the air. The Government of DKI Jakarta is making efforts to clean up wastein stream by forming a unit called the Stream Cleaner Unit under the auspices of the Environment Agency, to be responsible for the condition of solid waste in stream in the DKI Jakarta area. Pasar Rebo Sub-district is the first doorway for waste which is coming from Depok City. The purpoeses from this study is to determine how the waste transportation system is carried out by the Environmental Service and the Stream Cleaner Unit as the main institution dealing with waste problems in water bodies. The method of analysis used in this research is descriptive qualitative. The scope used in this research is the Water Stream of Pasar Rebo Sub-District, East Jakarta Administrative City. Based on research, supervisions and the number of used transportations needs to be increased. The awareness of the surrounding community also needs to be increased to create a healthy environment and clean water stream.